Study on the Feasibility of Development of Compang WesangVillage as a Tourism Village through a Local Human Resource Management Approach - Hersanius Kurnia Peong; Dominikus Seno; Dewi Sartika Umul; Yohana Cintami Lerry; Yohanes Paulus Hanny Wadhi (JURNAL AKADEMISI VOKASI, 2025)
This study examines the feasibility of developing Compang Wesang Village in East Manggarai Regency as a community-based tourism village destination through a human resource management approach. The selection of this topic is based on the importance of sustainable tourism development in rural areas and the gap between natural and cultural potential and the capacity of local human resources. This study uses a descriptive qualitative method with a case study design, through interview, observation, and documentation study techniques. The results of the study show that although the village has strong cultural and natural assets, tourism management has not been carried out professionally due to the lack of training, institutions, and a structured work system. The public's enthusiasm to participate is quite high, but it has not been properly facilitated by the government or external parties. These findings show the importance of combining HR management strategies with the principles of community empowerment so that the development of tourism villages can take place in a participatory, inclusive, and sustainable manner. Strengthening local institutions and the preparation of systematic training programs are important steps in encouraging sustainable economic and social growth.